Canva Application as a Learning Media for Human Anatomy Physiology - Hamdan Hariawan; Suratno Kaluku (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
Nursing education is one of the educations whose learning process through E-Learning during the covid-19 pandemic. The Canva application is an Android-based website that can be used as an online interactive learning medium. The purpose of this study was to analyze the effectiveness of the Canva application as an interactive learning medium for knowledge and practice of the anatomy and physiology of the respiratory and cardiovascular systems. This study is quasi-experimental with a pre-posttest approach with a control group. The sample in this study was 88 first-semester students of the Department of Nursing who were divided into two groups by simple random sampling. The research instruments used were questionnaires and observation sheets, and the results of this study were analyzed by the Mann-Whitney test, independent t-test, and N-Gain test. This study showed an increase in the average knowledge (p = 0.04) and practice (p = 0.012) in the group that was given the Canva Application media. However, in this study, the Canva application was ineffective as an interactive medium for learning anatomy and physiology (N-Gain = 30%). It is because learning with Canva can be affected by internet access, the ability of smartphone users, network availability, and internet quota.